Patronage and Support: Socio-Cultural Role of Kanheri Caves in the Evolving Interactions - Kishor Gaikwad (Ancient Asia, 2010)
A number of factors were responsible in the evolution of the first state craft in deccan locale. There were bound to be, several regional power centers beyond the main arena of Satvahna power. Their negotiation, complementing and supplementing each others need as well as with limited autonomy, enjoying their peripheral important status. Kanheri caves, specially the epigraphic evidences during Satvahna times, could be the best marker of variety of power specificities within deccan. These inscriptions made references to casts, gotras, communities, gahapaties as well as garini and kutumbini etc. These were all local social cultural forces were playing imperative roles in the larger eco-political ambiance of deccan. It's a kind of multidimensional relationship of mainstream political and cultural process, specially seprated to ecological setting. Surprisingly from these plaethora of inscriptions guilds and Satvahna royal house hold didn't carve out their space. Kanheri caves laid phenomenal role in trade and cultural interactions. The present paper as an attempt to explore socio cultural role of Kanheri caves in these interactions.